The Protection of Indonesian Migrant Workers under Fiqh Siyasah Dusturiyah - Ismail, Habib; Hakim, Dani Amran; Hakim, Muhammad Lutfi (Lentera Hukum, 2021)
The position of migrant workers is often seen as a weak party. To some extent, such migrant workers are regarded as similar to slaves. In Indonesia, the government has to protect all citizens, including those abroad who have the status of migrant workers. Migrant Workers’ Protection Law 18/2017 was issued to protect citizens as migrant workers. However, several migrant workers remained legally unprotected abroad. This study used the normative approach that aimed to discuss the protection of Indonesian migrant workers from two-fold, juridical and fiqh siyasah dusturiyah perspectives. While the government protected migrant workers by issuing Law 18/2017, it has more specifically provided directions and objectives to protect migrant workers. This Law ensures human rights for migrant workers despite legal, economic, and social protection for them and their families. Then, the protection of migrant workers from fiqh siyasah dusturiyah should be under the four principles of the workforce in Islam: human independence, human dignity, justice, and the clarity of the contract and wage transaction. KEYWORDS: Indonesian Migrant Workers, Right to Work, Islamic Law.